Band Edge Control of Quasi‐2D Metal Halide Perovskites for Blue Light‐Emitting Diodes with Enhanced Performance. (8th August 2021) - Worku, Michael; Ben‐Akacha, Azza; Sridhar, Samanvitha; Frick, Jordan R.; Yin, Shichen; He, Qingquan; Robb, Alex J.; Chaaban, Maya; Liu, He; Winfred, J. S. Raaj Vellore; Hanson, Kenneth; So, Franky; et al.
Abstract: Perovskite light‐emitting diodes (PeLEDs) have received great attention for their potential as next‐generation display technology. While remarkable progress has been achieved in green, red, and near‐infrared PeLEDs with external quantum efficiencies (EQEs) exceeding 20%, obtaining high performance blue PeLEDs remains a challenge. Poor charge balance due to large charge injection barriers in blue PeLEDs has been identified as one of the major roadblocks to achieve high efficiency. Here band edge control of perovskite emitting layers for blue PeLEDs with enhanced charge balance and device performance is reported. By using organic spacer cations with different dipole moments, that is, phenethyl ammonium (PEA), methoxy phenethyl ammonium (MePEA), and 4‐fluoro phenethyl ammonium (4FPEA), the band edges of quasi‐2D perovskites are tuned without affecting their band gaps. Detailed characterization and computational studies have confirmed the effect of dipole moment modification to be mostly electrostatic, resulting in changes in the ionization energies of ≈0.45 eV for MePEA and ≈ −0.65 eV for 4FPEA based thin films relative to PEA‐based thin films. With improved charge balance, blue PeLEDs based on MePEA quasi‐2D perovskites show twofold increase of the EQE as compared to the control PEA based devices. Abstract : Rational band edge energy level control of quasi‐2D metal halide perovskites by modifying the dipole moments of organic spacer cations is shown to improve the external quantum efficiency of blue perovskite light‐emitting diodes by more than twofold.